Meningkatkan Kualitas Mentor Melalui Pelatihan Pengelolaan Emosi - Nasrullah, Asmaul Husnah; NFH, Alifya; B, Muhammad Fajar; Wardani, Ayu Tri; Hamda, Hamda (Jurusan Teknik Informatika dan Komputer, 2025)
Emotional intelligence constitutes a critical determinant in the effectiveness of mentor–mentee relationships, particularly within the domains of character development, psychosocial support, and interpersonal communication. This community engagement initiative aimed to enhance the emotional competence of university students serving as mentors through an emotion regulation training program employing participatory and educational approaches. A total of 50 students from the Informatics Education and Computer Engineering programs at Universitas Negeri Makassar participated in the program, which included a pre-test, delivery of conceptual material, reflective discussions, workshops on emotion regulation techniques, and role-play simulations. Evaluation results indicated a significant improvement in emotional awareness and regulation skills, as evidenced by pre- and post-test comparisons and qualitative participant feedback. The training proved effective in cultivating mentor capacity that is not only cognitively competent but also emotionally adaptive, thereby facilitating productive and sustainable mentoring relationships.